Interview with Nato Thompson. Issue 1 (1st December 2015) - Coombs, Gretchen; Thompson, Nato
Nato Thompson, Chief Curator at Creative Time, served as the moderator for the session, 'The Ethics of Social Practice', at the 2015 College Art Association annual conference in New York City. We invited him to respond to a series of questions focused on ethics, social practice and his role as a curator in the form of an interview for this issue.